Spatial Layouts of Low‐Entropy Hydration Shells Guide Protein Binding - Lin Yang; Shuai Guo; Chenchen Liao; Chengyu Hou; Shenda Jiang; Jiacheng Li; Xiaoliang Ma; Liping Shi; Lin Ye; Xiaodong He (Global Challenges, 2023)
Abstract Protein–protein binding enables orderly biological self‐organization and is therefore considered a miracle of nature. Protein‒protein binding is driven by electrostatic forces, hydrogen bonding, van der Waals force, and hydrophobic interactions. Among these physical forces, only hydrophobic interactions can be considered long‐range intermolecular attractions between proteins due to the electrostatic shielding of surrounding water molecules. Low‐entropy hydration shells around proteins drive hydrophobic attraction among them that essentially coordinate protein‒protein binding. Here, an innovative method is developed for identifying low‐entropy regions of hydration shells of proteins by screening off pseudohydrophilic groups on protein surfaces and revealing that large low‐entropy regions of the hydration shells typically cover the binding sites of individual proteins. According to an analysis of determined protein complex structures, shape matching between a large low‐entropy hydration shell region of a protein and that of its partner at the binding sites is revealed as a universal law. Protein‒protein binding is thus found to be mainly guided by hydrophobic collapse between the shape‐matched low‐entropy hydration shells that is verified by bioinformatics analyses of hundreds of structures of protein complexes, which cover four test systems. A simple algorithm is proposed to accurately predict protein binding sites.